Produccion del Tema “Kibo” Banda “Tales Of Dawn - Estrella Cárdenas, Carlos Arturo (2012)
Melodic Metalcore band of “Tales of Dawn”, was born on the 1st. December 2011 in Quito, Ecuador and consists of: Erik Ortiz first guitar and lyrical voice. Carlos Estrella second guitar and throaty voice. Carlos Román percussion (drums). Mauricio Paredes DJ and sequences. Andrés Aguirre vocals, throaty and lyrical. Geovanna Reyes guest artist, choirs. As of March 3th, 2012, the band “Tales of Dawn” began to work on what will be its first single. On the topic called KIBO, they apply technical knowledge acquired in the classroom music of the institution and the original end product is delivered to the academic authorities...